A mai nyugdíjhelyzet megoldási lehetőségei a Generali Biztosító Zrt. termékein keresztül - Nagy Dóra (2015)
I chose this topic for my thesis because we can hear more and more about the pension sys-tem being unsustainable. The state finds it increasingly difficult to finance pensions since the ratio of pensioners to active workers is growing steadily. This situation is further ag-gravated by the worsening unemployment rate, the reduction in births, and the aging so-ciety. The state is striving to alleviate the situation by adopting more preferential family policies and gradually pushing up the retirement age. This is not necessarily a good solu-tion since, due to the incredible amount of stress and the unhealthy lifestyles resulting from our fast moving world, many people may not even live to the retirement age. This is why a change of attitude is necessitated so that people should realise the importance of saving up for their pensioners’ years at a young age and enjoy their elderly years at a good standard of living. Having seen all these, my curiosity was aroused and I wished to know how much people in general and the young generation specifically are interested in self-provision. My aim was to map the opportunities open for self-provision. I furthermore aimed to describe the evolution and history of the Hungarian pension system while highlighting the problems endangering pensions as well as characterising the main pillars of the pension system. I additionally compared not only the various opportunities for saving up but also listed the various products offered by Generali Biztosító Zrt. to this end. I studied several sources when preparing my thesis, among other things, technical literature and textbooks, economic journals and materials produced by Generali Biztosító Zrt. I published my questionnaire on the Internet and recorded the responses by Internet tools. I furthermore made use of Microsoft Office Excel to analyse the generated data. My questionnaire was completed by 137 respondents, the majority of whom belong to the age group between 18 and 30. This was especially delightful to me since it is my own age group and this age group is still in the position to act efficiently in order to cater for their elderly years. My survey suggests that self-provision is important for everyone. It has also been revealed that saving up is found to be important though limited by people’s income. At a younger age, people might still give prominence to building up a career and then starting a family. However, the middle-aged group has passed through such situations in life, and the nearer they get to the retirement age, the more importance they attach to self-provision. In conclusion, we can state that self-provision is indeed important since it is not the same at all in what circumstances we can reach our elderly years.